11th IEEE/ACM International Symposium on Modeling, Analysis and Simulation of Computer Telecommunications Systems, 2003. MASCOT
DOI: 10.1109/mascot.2003.1240667
|View full text |Cite
|
Sign up to set email alerts
|

Managing flash crowds on the Internet

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
1
2

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 5 publications
0
79
1
2
Order By: Relevance
“…Using an admission control mechanism to prevent additional overload has also been suggested [123]. On a more global scale, adequate caching mechanisms can alleviate the problem [33].…”
Section: Flash Crowdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an admission control mechanism to prevent additional overload has also been suggested [123]. On a more global scale, adequate caching mechanisms can alleviate the problem [33].…”
Section: Flash Crowdsmentioning
confidence: 99%
“…Slightly lower down we start seeing navigational queries targeting more traditional companies and institutions, such as "walmart" (22), "southwest airlines" (31), and "target" (33). These typically have only one main variant, without Internet address trimmings.…”
Section: Transactional Queriesmentioning
confidence: 99%
“…The flashcrowd starts at the beginning of the increase and finishes at the end of the increase. Similar definitions are also used [3], [7] in modeling web server workloads. As illustrated in Figure 1, our flashcrowd model consists of four components: the arrival time, which is the time between the creation of a swarm and the start of a flashcrowd; the duration, which is the time between the start and the end of the increase; the plateau period, which is the time period with limited churn immediately after a flashcrowd ends; and the magnitude, which indicates the significance of a flashcrowd in terms of the increase.…”
Section: A Model Of Bittorrent Flashcrowdsmentioning
confidence: 99%
“…Consequently, the longest jobs in this trace are limited to 18 hours (since a job that exceeds its runtime estimate is killed by the system). However, in a real system, it takes some time to propagate the instruction to kill a job to all the nodes 2 . Therefore the trace indicates that some jobs run for a bit more than 18 hours.…”
Section: Example Of a Butterfly Effectmentioning
confidence: 99%
“…Of course, in these particular cases, high-load conditions may be more important and meaningful than normal conditions; if this is the case, they should be the focus of study rather than being eliminated as suggested below. For example, Ari et al model such activity, which they call "flash crowds", with the aim of evaluating schemes to survive them [2].…”
Section: Generalizingmentioning
confidence: 99%